MENINGKATKAN KEMAMPUAN BEREMPATI ANAK USIA 5-6 TAHUN MELALUI COOPERATIVE LEARNING - S, Fitri Wulandari; Rosidah, Laily; Maryani, Kristiana (JIV-Jurnal Ilmiah Visi, 2017)
Emphatic abilities are abilities to understand other people’s feelings. Emphatic is built based on their own awareness, the more open children are to their emotions, the better they are in understanding others’ feelings. Low emphatic abilities are found in 5-6 years old children at PAUD Bina Bangsa Islamic School, they can be seen from children’s daily habit at schools which cannot show understanding of their friends’ feelings and how to act to others. Due to that reason, cooperative learning implementation is needed to stimulate cooperation and interaction in children so that they can escalate their emphatic abilities well. This research was conducted on 13-10 April 2017 at PAUD Bina Islamic School using action research method conducted in two cycles with success criteria of 70%. The objective is to find out how learning cooperative processes escalate 5-6 years old children’s emphatic abilities. Based on research results obtained, their emphatic abilities can be escalated through cooperative learning with 22% on preaction, then the emphatic abilities are getting higher in the first cycle to 50.43%, and in the second cycle it is increasing as well to 96.42%. Based on data acquired, it can be inferred that 5-6 years old children’s abilities can be escalated through cooperative learning.